Intikhab-e-Kalam : Ismail Merathi - Ismail Merathi; Edited and introduced by Rauf Parekh (Karachi Oxford University Press, 2015)
This selection of poems from Ismail Meeruthi who wrote poems primarily for school children have been a perennial favourite. They range from nursery rhymes to didactic, but charming poems for students of the primary level. The school textbooks for Urdu, Ismail Meeruthi designed grew outmoded, but the poems themselves have survived because of their simplicity, their rustic charm and their freshness, which had a different aspect from the stylized and Persianised poetry patronized by the grown ups.
Keywords: Urdu Literature - Poetry -- Poetry in Urdu -- Urdu Literature - Poetry -- Intikhab e Kalam : Ismail Merathi